KERAJINAN TENUN SONGKET MELAYU RIAU UNTUK PELESTARIAN KEARIFAN LOKAL - Guslinda, Guslinda (Jurnal Pendidikan Guru, 2017)
Riau Malay songket weaving craft is the cultural heritage from generation to temurum which must be maintained kelestarianya. Riau Malay songket is the craft laden with wisdom values and also valuable in the universe (universal). The presence of the Malay songket weaving craft which manifested itself in various forms and shades of course also have a philosophy and symbolism in public life. Philosophy and symbolism is evident from the style and yeast from the Riau Malay songket. The forms of the Malay Songket Weaving craft materialized in the form of clothes and belongings shovenir used in everyday life and also for traditional ceremonies. Use of Riau Malay songket can certainly be used as a medium for the preservation of culture based on local wisdom